A proposed English proficiency test in vocabulary for six selected Asian student groups - Francisco, Violeta V. 1947- (1972)
A proposed English Proficiency Test in Vocabulary is conducted to appraise a person's command of the English speaking vocabulary. The test is significant although it cannot be used as a lone indicator of the ability to speak and write effectively, for no one can comprehend or express thoughts clearly if he does not have a command of the vocabulary of the language. The study is designed for the six largest groups of foreign students enrolled in the University of the Philippines namely, the Thais, the Pakistanis, the Indonesians, the Chinese, the Vietnamese, and the Japanese. The test when used with linguistically prepared objective tests dealing with representative samples of pronunciation and grammatical problems, may be used to screen Asian candidates for admission to the University of the Philippines and other institutions of higher learning in the country.